Sistem Informasi Penjualan pada Bengkel Sumber Jaya Motor - Ryan Christy (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Sumber Jaya Motor Workshop in running its business has still use manual recording system. This study is used to facilitate the Sumber Jaya Motor Workshop in recording sales using the appropriate system, by creating a simple desktop-based system that can be used sustainably for the needs of the Sumber Jaya Motor Workshop. This study employs the system development techniques of prototyping, analysis and design using UML implemented with VB.net language and SQL Server database, and testing with blackbox testing. The results of this study are a sales information system designed to prevent data entry errors and the occurrence of fraud, as well as to facilitate the systematic recording of sales data..